Object discretizations in higher dimensions - Brimkov, VE; Andres, E; Barneva, RP (Elsevier, 2002)
In this paper we study discretizations of objects in higher dimensions. We introduce a large class of object discretizations, called k-discretizations. This class is natural and quite general, including as special cases some known discretizations, like the standard covers and the naive discretizations. Various results are obtained in the proposed general setting. (C) 2002 Elsevier Science B.V. All rights reserved.
9th International Conference on Discrete Geometry for Computer Imagery (DGCI 2000) -- DEC 13-15, 2000 -- UPPSALA, SWEDEN
Keywords: object discretization; supercover; standard cover; naive discretization; k-discretization